Sacubitril/valsartan versus ramipril for patients with acute myocardial infarction: win‐ratio analysis of the PARADISE‐MI trial. (14th September 2022) - Berwanger, Otavio; Pfeffer, Marc; Claggett, Brian; Jering, Karola S.; Maggioni, Aldo P.; Steg, Philippe Gabriel; Mehran, Roxana; Lewis, Eldrin F.; Zhou, Yinong; van der Meer, Peter; De Pasquale, Carmine; Merkely, Béla; et al.
ABSTRACT: Aim: The win ratio can incorporate different types of outcomes and enhance statistical power, making it a useful method for analysing composite outcomes in cardiovascular trials. The application of this approach to the PARADISE‐MI trial provides an additional perspective into understanding the effects of sacubitril/valsartan in patients with acute myocardial infarction. Methods and results: We conducted a post‐hoc analysis of the PARADISE‐MI trial, which randomly assigned patients with acute myocardial infarction complicated by a reduced left ventricular ejection fraction, pulmonary congestion, or both to receive either sacubitril/valsartan (97 mg of sacubitril and 103 mg of valsartan twice daily) or ramipril (5 mg twice daily) in addition to guideline‐recommended therapy. The principal composite outcome was analysed in the hierarchical order of death due to cardiovascular causes, first hospitalization for heart failure, and first outpatient episode of symptomatic heart failure. We included events confirmed by the clinical events classification (CEC) committee as well as events identified by investigators that did not meet study definitions. Results were analysed by the unmatched win‐ratio method. A win ratio that exceeds 1.00 reflects a better outcome. A total of 5661 patients underwent randomization; 2830 were assigned to receive sacubitril/valsartan and 2831 to receive ramipril. The hierarchical analysis of the principal composite outcome demonstrated a larger number of wins (1 265 767 [15.7%]) than losses (1 079 502 [13.4%]) in the sacubitril/valsartan group (win ratio of 1.17, 95% confidence interval [CI] 1.03–1.33; p  = 0.015). Sensitivity analyses using alternative definitions of the composite outcome showed results similar to those of the principal analysis, except for analysis restricted to events that met CEC definitions (win ratio of 1.11, 95% CI 0.96–1.30; p  = 0.16). Conclusion: In this post‐hoc analysis of the PARADISE‐MI trial using the win ratio and including investigator‐identified events not having CEC confirmation, sacubitril/valsartan was superior to ramipril among high‐risk survivors of acute myocardial infarction. Abstract : PARADISE‐MI win ratio analysis summary. CEC, clinical event classification; CI, confidence interval; CV, cardiovascular; HF, heart failure.